2010
DOI: 10.2147/opth.s5901
|View full text |Cite
|
Sign up to set email alerts
|

The outer limiting membrane (OLM) revisited: clinical implications

Abstract: The outer limiting membrane (OLM) is considered to play a role in maintaining the structure of the retina through mechanical strength. However, the observation of junction proteins located at the OLM and its barrier permeability properties may suggest that the OLM may be part of the retinal barrier. Material and methods: Normal and diabetic rat, monkey, and human retinas were used to analyze junction proteins at the OLM. Proteome analyses were performed using immunohistochemistry on sections and flat-mounted r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(37 citation statements)
references
References 21 publications
1
34
0
2
Order By: Relevance
“…In the retina, labeling was detected in the outer limiting membrane (OLM) (arrowhead in Fig. 2F ), which has been previously shown to contain both AJ and TJ proteins [20] , and along the junctions between retinal pigmented epithelial cells (arrow in Fig. 2F ).…”
Section: Resultsmentioning
confidence: 90%
“…In the retina, labeling was detected in the outer limiting membrane (OLM) (arrowhead in Fig. 2F ), which has been previously shown to contain both AJ and TJ proteins [20] , and along the junctions between retinal pigmented epithelial cells (arrow in Fig. 2F ).…”
Section: Resultsmentioning
confidence: 90%
“…Herein we address the implication of the overlooked outer barriers in diabetic retinopathy in a rat model of type2 diabetes. We have recently shown that the OLM is not only formed by adherent junctions between glial Müller cells and photoreceptors but also contains heterotypic tight-junctions, suggesting that the OLM should be considered as part of the outer retinal barrier [6] . However, what regulates this barrier and what are the consequences of OLM barrier function alteration in the course of diabetes has not been explored.…”
Section: Discussionmentioning
confidence: 99%
“…The apical side of RPE faces the photoreceptor outer segments of the neuroretina, and the basolateral side lies on Bruch's membrane, which separates the RPE from the underlying fenestrated endothelium of the choriocapillaris [5] . We have recently evidenced that tight-like junctions containing occludin are present also at the OLM, mainly between Müller glial cells and cones, the only photoreceptors of the macula [6] . Among the molecules involved in TJ formation and maintenance, the critical role of the PAR6/PKCζ/PAR3 scaffold complex in cell polarity has been extensively studied [7] – [13] .…”
Section: Introductionmentioning
confidence: 99%
“…Muller glia form adherens junctions with PR demarking the junction between outer nuclear and IS layers (Bunt-Milam et al, 1985;Williams et al, 1990). These junctions and the band of actin filaments running between them form a readily visible line in histological preparations of the retina and historically were given the misnomer of the outer limiting membrane (Williams et al, 1990;Omri et al, 2010). Muller glia extend microvilli past this junctional belt.…”
Section: Retinamentioning
confidence: 99%